Association between markers of immune response at hospital admission and COVID‐19 disease severity and mortality: A meta‐analysis and meta‐regression. Issue 2 (28th September 2020) - Khinda, Jaskaran; Janjua, Naveed Z.; Cheng, Shannon; van den Heuvel, Edwin R.; Bhatti, Parveen; Darvishian, Maryam
Abstract: Background: To determine the utility of admission laboratory markers in the assessment and prognostication of coronavirus disease‐2019 (COVID‐19), a systematic review and meta‐analysis were conducted on the association between admission laboratory values in hospitalized COVID‐19 patients and subsequent disease severity and mortality. Material and Methods: Searches were conducted in MEDLINE, Pubmed, Embase, and the WHO Global Research Database from December 1, 2019 to May 1, 2020 for relevant articles. A random effects meta‐analysis was used to calculate the weighted mean difference (WMD) and 95% confidence interval (95% CI) for each of 27 laboratory markers. The impact of age and sex on WMDs was estimated using meta‐regression techniques for 11 markers. Results: In total, 64 studies met the inclusion criteria. The most marked WMDs were for neutrophils (ANC) at 3.82 × 10 9 /L (2.76, 4.87), lymphocytes (ALC) at −0.34 × 10 9 /L (−0.45, −0.23), interleukin‐6 (IL‐6) at 32.59 pg/mL (23.99, 41.19), ferritin at 814.14 ng/mL (551.48, 1076.81), C‐reactive protein (CRP) at 66.11 mg/L (52.16, 80.06), D‐dimer at 5.74 mg/L (3.91, 7.58), LDH at 232.41 U/L (178.31, 286.52), and high sensitivity troponin I at 90.47 pg/mL (47.79, 133.14) when comparing fatal to nonfatal cases. Similar trends were observed comparing severe to non‐severe groups. There were no statistically significant associations between age or sex and WMD for any of the markers included in the meta‐regression. Conclusion: The results highlight that hyper inflammation, blunted adaptive immune response, and intravascular coagulation play key roles in the pathogenesis of COVID‐19. Markers of these processes are good candidates to identify patients for early intervention and, importantly, are likely reliable regardless of age or sex in adult patients.